2018
DOI: 10.1038/s41598-018-19500-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre-conception maternal erythrocyte saturated to unsaturated fatty acid ratio predicts pregnancy after natural cycle frozen embryo transfer

Abstract: The environment for embryo implantation and fetal growth and development is affected by maternal nutritional, metabolic and health status. The aim of this prospective, cohort study was to test whether plasma metabolic and inflammatory biomarkers can predict pregnancy resulting from in vitro fertilisation (IVF). Women with a natural menstrual cycle undergoing frozen embryo transfer (FET) were recruited and fasting baseline blood samples were collected a mean of 3.4 days prior to the luteinising hormone (LH) sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Pugh et al 9 reported a study including 848 hyperlipidemia women and 380 control women and found a 19−36% decrease in the probability of conception per cycle for women with abnormal lipoprotein levels. It was reported that serum lipids levels were associated with embryo quality and pregnancy rates and that higher serum TG level was associated with a lower chance of live birth 10,11 . Some studies have confirmed that hyperlipidemia was negatively associated with the cLBR of patients undergoing in vitro fertilization or intracytoplasmic sperm injection 5,9 .…”
Section: Discussionmentioning
confidence: 98%
“…Pugh et al 9 reported a study including 848 hyperlipidemia women and 380 control women and found a 19−36% decrease in the probability of conception per cycle for women with abnormal lipoprotein levels. It was reported that serum lipids levels were associated with embryo quality and pregnancy rates and that higher serum TG level was associated with a lower chance of live birth 10,11 . Some studies have confirmed that hyperlipidemia was negatively associated with the cLBR of patients undergoing in vitro fertilization or intracytoplasmic sperm injection 5,9 .…”
Section: Discussionmentioning
confidence: 98%
“…Oocyte competence, which is the oocyte's potential for completing meiosis, generating a zygote, and developing into a preimplantation embryo, profoundly depends on the contents of the oocyte's immediate surroundings 24–26 . As stated previously, an erythrocyte FA profile is an alternative indicator of tissue FAs over the previous 3 months, and erythrocytes have been suggested to function as potential circulating reservoirs for some essential PUFAs, such as AA and DHA 27 . Moreover, studies have demonstrated that the FA composition of erythrocytes could represent that of follicular fluid 28 .…”
Section: Maternal Erythrocyte Fatty Acid Composition and Reproductive...mentioning
confidence: 92%
“…These findings suggest that the content of trans FAs in erythrocytes could be informative for the prediction of oocyte developmental competence. In a similar study, Onyiaodike et al 27 examined whether the FA composition of erythrocytes could be predictive of clinical pregnancy in 143 individuals who were submitted to a natural IVF cycle and frozen embryo transfer. The study found a positive link between the ongoing pregnancy and the ratio of saturated FAs to unsaturated FAs at a mean of 3.4 days before the surge in luteinizing hormone (LH) that triggers ovulation 20–30 h later.…”
Section: Maternal Erythrocyte Fatty Acid Composition and Reproductive...mentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrocyte fatty acids are considered more accurate and objective than FFQ [ 19 ]. Compared to plasma fatty acids, erythrocyte fatty acids are not affected by fasting [ 20 , 21 ]. Therefore, this study aimed to assess the prospective association of maternal erythrocyte PUFA with offspring allergies in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%